IMPLEMENTASI TQM TERHADAP MUTU INSTITUSI DALAM LEMBAGA PENDIDIKAN - Suhermanto, Suhermanto; Anshari, Anshari (JURNAL AL-TANZIM, 2018)
Earing the word education is certainly no stranger to the public. Education is addressed with school and learning. The word education in terms of language is derived from the word "pedagogy" namely "paid" which means child and "agogos" which means guiding. So pedagogy or education is the science of guiding children. Education can also be defined as a process of changing the attitude and behavior of a person or group in an effort to mature a human being or a student through teaching and training efforts. The word management is often heard in our daily lives. Management is used to assist us in doing things. The role of management is needed in daily life which is intended to regulate all work. Through management, all work can be done and done well and systematically. We usually get quality when we discuss about industries related to the provision or delivery of services. The field of education is one area that provides services to its customers. The intended customers in the world of education are divided into 3 groups, namely primary customers (directly involved, namely students), secondary customers (who support education such as parents), and tertiary customers (indirectly involved but have an important role in education, namely employees, community, and government).